Validation of Course Ontology Elements for Automatic Question Generation - N. H. Ibrahim Teo; M. S. Joy (European Alliance for Innovation (EAI), 2017)
Recent research has led to the emergence of ontology-based question generation and aims to benefit instructors by providing support and intelligent assistance for the automatic generation of questions. However, existing ontologies are not designed mainly for this purpose, and the concern is that an ontology will not be competent enough to act as a semantic source for the question generation process. Therefore, the aim of this work is to validate how well the elements represented in course ontology can be used for the purpose of automatic question generation. In this work, we choose to validate Operating System ontologies and identify related question sources from textbooks on this subject as competency questions. Finally, the result shows that the evaluated ontologies can provide knowledge for generating useful assessment questions. Furthermore, the list of categorized question templates and their variations are generated using a strategy based on the validated ontology.